Analysis of Business Strategy and Operations of Petis Pasean Business from the Perspective of Islamic Business Ethics - Ghafiratun Ni’am El Maulidiyah; Abdur Rohman (Penerbit Hellow Pustaka, 2025)
This study aims to analyze the business and operational strategies of the Pasean petis business as an effort to strengthen the local economy in Pasean District, Pamekasan Regency. Petis Pasean is a processed fish product typical of Madura that has great potential to be developed as a superior regional product. Through a descriptive qualitative approach, data was collected through interviews, observations, and documentation studies of business actors, especially the Bu Siti Fish Petis producer. The results of the analysis show that the current strategy is still traditional, with limitations in marketing, production management, and resource management. However, there is a great opportunity for development through product innovation, brand strengthening, and the use of digital media as a means of promotion. From an operational perspective, production efficiency and raw material quality are the keys to increasing competitiveness. In conclusion, strengthening business and operational strategies in an integrated manner has the potential to encourage the growth of the Pasean petis business and make a significant contribution to the local economy.